2014
DOI: 10.1007/s11207-014-0533-7
|View full text |Cite
|
Sign up to set email alerts
|

An Observed Decline in the Amplitude of Recent Solar-Cycle Peaks

Abstract: There has been much speculation about the extended minimum between Solar Cycles 23 and 24. Cycle 24 itself has been unusually weak compared with recent cycles. We present quantitative evidence for the weakness of both Cycles 23 and, particularly, 24. The data are objective indices derived from precision photometric images obtained on a daily basis at the San Fernando Observatory. These data form the longest running, homogeneous photometric record known to us. We show sunspot areas from red images and facular/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…FA started to increase since the beginning of 1999 until the middle of 2009 and it started to increase again after the year 2010. Our results for SSCs, SG numbers, FA and Ca II K-flux support the analysis of Kilcik et al (2011), de Toma et al (2004,2013) and Chapman et al (2014).…”
Section: Facular Area and Ca II K-fluxsupporting
confidence: 92%
“…FA started to increase since the beginning of 1999 until the middle of 2009 and it started to increase again after the year 2010. Our results for SSCs, SG numbers, FA and Ca II K-flux support the analysis of Kilcik et al (2011), de Toma et al (2004,2013) and Chapman et al (2014).…”
Section: Facular Area and Ca II K-fluxsupporting
confidence: 92%
“…Our detailed analysis of the variation of TSI fluxes in the cycles 22 -24 showed that the assumption in Svalgaard (2013) which was done on observational data of Penn and Livingston (2006), (2011) and Chapman et al . (2014) is true: at one and the same level of F 10.7 the value of TSI at the cycles 23 -24 increases, see Fig.…”
Section: Discussionmentioning
confidence: 89%
“…It increases the radiation flux from the photosphere due to the decreasing of deficit of bright photosphere's flux in dark spots. Moreover, the relative amplitudes of the total areas of spots in the cycle's maximums decrease in the cycles 23+24 compared to the cycle 22, and the ratio of total areas of faculae to total areas of spots in the cycle 24 is growing according to Chapman et al . (2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study provides evidence for a possible link between the spatial evolution of magnetic flux emergence and rate of solar flares, which is consistent with our results (see also Joshi et al 2006b). In particular, many irregularities in sunspot manifestations during cycle 23 have been well observed and extensively studied (Russell et al 2010;Lukianova & Mursula 2011;Lefèvre & Clette 2011;Clette & Lefèvre 2012;Livingston et al 2012;Chapman et al 2014) that finally point to the complexities of underlying solar dynamo processes. Lefèvre & Clette (2011) found that cycle 23 is quite distinguishable from the previous cycle in terms of significant deficit in small sunspot, while large-scale spots remained largely unaffected.…”
Section: Discussionmentioning
confidence: 99%